Wage, Returns to Ownership, and Fee Responses to Physician Supply - Headen, Alvin E. (The Review of Economics and Statistics, 1990)
The labor and entrepreneurial components of reported physician net income are separated in an analysis of input and output market performance. A wage equation, corrected for selectivity bias, is estimated for employee physicians and the results indicate that the performance of the labor market for primary care physicians is consistent with competitive theory. The parameters are used to predict opportunity wage rates for self-employed physicians. Differences between net income per hour and the predictions indicate that 16 percent of net income from practice is attributable to entrepreneurship. Evidence of negative selectivity into employee status is also found. Copyright 1990 by MIT Press.